Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How do I simplify the following expression:

$$\log_2(2x+1) - 5\log_4(x^2) + 4\log_2(x)$$

That's it, please help me ok?

share|cite|improve this question
up vote 3 down vote accepted



as $\log a+ \log b=\log ab,m\log a=\log a^m$ and $\log_yz=\frac{\log_xz}{\log_xy}$ where $x\neq 1$ as $\log_1y$ is not defined.







share|cite|improve this answer

Suppose that $x>0$ is some number, and $\log_4x=y$. That means that $4^y=x$. Now $4=2^2$, so $x=4^y=\left(2^2\right)^y=2^{2y}$, and that means that $\log_2x=2y$. In other words, we’ve just demonstrated that for any $x>0$, $\log_2x=2\log_4x$.

Now you have $\log_2(2x+1)-5\log_4x^2+4\log_2x$, which mixes logs base $2$ with logs base $4$; it would be much easier to simplify if all of the logs were to the same base. Use the result of the first paragraph to change $\log_2(2x+1)$ to $2\log_4(2x+1)$ and $\log_2x$ to $2\log_4x$; then you have


and you can use the usual properties of logs to express this as the log base $4$ of a single expression.

Going back to $\log_2x=2\log_4x$, if you happen to notice that $2\log_4x=\log_4x^2$, you simply replace $5\log_4x^2$ by $5\log_2x$ to get


which is even easier to simplify. The answers that you get by these two approaches won’t be identical, since one will be a log base $4$ and the other a log base $2$, but they’ll be equal, and you can use the relationship $\log_2x=2\log_4x$ to verify this.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.